4 - The Multiparty Promise Betrayed: The Failure of Neo-Liberalism in Malawi : DOI: 10.4314/ad.v29i2.22194 - Khembo, Nixon S. (Africa Development, 2004)
The advent of multiparty politics in Malawi in June 1993 was not immediately perceived as the harbinger of a myriad of political twists and turns that have now confounded many. Emerging from the grip of a 30-year-old totalitarian regime, Malawians had every reason to jubilate when the pro-multiparty politics movement triumphed after the June 14, 1993 national referendum results were announced in which the movement was awarded a 64 percent victory of the vote cast to allow multiparty politics to be re-introduced into the country. First, this paper argues that the new multiparty system of government in the country is caught up in neo-liberal and neo-patrimonial puzzles that undermine the process of démocratisation. Second, that this state of affairs is rooted in the failure of neo-liberalism in Malawi; thus, the Malawian case has demonstrated that when neo-liberalism flounders, despotism recurs in a cycle of regime change. Third, that the selective application and the strange interpretation of constitutional law in Malawian politics is a clear manifestation of the existence, and draconian domination, of this despotism. Fourth, and finally, that liberal ideology, by its very nature, is a major drawback to the creation of a truly just state in Malawi.